PERANAN KERAJAAN ISLAM DALAM PERKEMBANGAN PENDIDIKAN DI INDONESIA - Safei, Safei (AULADUNA: Jurnal Pendidikan Dasar Islam, 2015)
Abstract: Before the arrival colonialism, in the Nusantara it has been established some Islamic governments that have developed education with Islamic education system. A system that is different from the colonial education system, especially the Netherlands. Islamic education system that has grown and evolved with the development of Islam in the archipelago which was once based in mosques, surau, langgar, or pesantren. Originally these places are double in function, that is, as the place for worship and as the center for the study of religious sciences including education. Many parties acknowledged that Islamic educational institutions in the Islamic kingdom is an educational institution that has gained national life, and very meritorious for the advancement of Indonesia after independence. The facts show that the leaders of this nation little early backgrounds were students and scholars. Abstrak: Sebelum kedatangan penjajah, di Nusantara telah berdiri beberapa kerajaan Islam yang telah mengembangkan pendidikan dengan sistem pendidikan Islam, suatu sistem yang berbeda dengan sistem pendidikan kolonial terutama Belanda. Sistem pendidikan Islam itu telah tumbuh dan berkembang seiring dengan perkembangan Islam di Nusantara itu dulunya berpusat di masjid, surau, langgar, atau pesantren. Pada mulanya tempat-tempat tersebut berfungsi ganda tempat ibadah juga sebagai pusat kegiatan pengkajian ilmu-ilmu agama termasuk pendidikan. Oleh banyak kalangan diakui bahwa lembaga pendidikan Islam pada masa kerajaan Islam merupakan lembaga pendidikan yang telah ikut serta mencerdaskan kehidupan bangsa, dan sangat berjasa bagi kemajuan bangsa Indonesia setelah kemerdekaan. Fakta-fakta menunjukkan bahwa pemimpin-pemimpin awal bangsa ini tidak sedikit berlatar belakang santri dan ulama.